Immunosensor for the diagnosis of Chagas' disease - Ferreira, AAP; Colli, W.; da Costa, P. I.; Yamanaka, H. (Elsevier B.V., 2005)
Trypanosoma cruzi proteins from epimastigote membranes, herein referred as antigens, have been used for the construction of an amperometric immunosensor for serological diagnosis of Chagas' disease. The proteins used had a molecular mass ranging from 30 to 100 kDa. The gold electrode was treated with cysteamine and glutaraldehyde prior to antigen immobilization. Antibodies present in the serum of patients with Chagas' disease were captured by the immobilized antigens and the affinity interaction was monitored by chronoamperometry at a potential of -400 mV (versus Ag pseudo-reference electrode) using peroxidase-labeled IgG conjugate and hydrogen peroxide, iodide substrate. The incubation time to allow maximum antigen-antibody and antibody-peroxidase-labeled IgG interactions was 20 min with a reactivity threshold at -0.104 mu A. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: T. cruzi; immunosensor; Chagas' disease